Aplikasi Penilaian Siswa Berbasis Web Menggunakan Rapid Application Development (RAD) Dan Pengujian Blackbox - Aqidatul Izzah Chairul; Kecitaan Harefa (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Information technology is needed to be able to speed up the work carried out by the management of SMP Negeri 2 Kota Tangerang Selatan. The goal to be achieved by researchers is the application of a web-based academic assessment information system. This study uses a qualitative approach and the type of research is descriptive with the aim of providing an overview of a particular symptom. Data collection techniques through literature study, observation, and interviews. The research method used is the rapid application development (RAD) method. With this research, the results of a web-based academic assessment information system were obtained which included assessment reports, attendance, grade summaries, and reports that could be accessed online. So that this system can be implemented by SMP Negeri 2 Kota Tangerang Selatan.